An integrated smart thermo-chemical energy network. (October 2022) - Giampieri, A.; Roy, S.; Shivaprasad, K.V.; Smallbone, A.J.; Roskilly, A.P.
Abstract: Managing the intermittency of renewable sources together with transient (hourly to daily to seasonal) energy demands is one of the principal challenges of delivering a net-zero energy system. Smart multifunctional thermo-chemical energy networks represent an alternative energy network and storage system, a solution based on the distribution of energy via thermo-chemical material rather than thermal energy, gas, fuels or electricity– an option that has scope for integrated short- and long-term energy storage. This is the first research work to realise such a system and demonstrate how it might operate using smart control strategies and how thermo-chemical fluids (TCFs) can be used as a medium for timely energy storage and distribution. The experimental study also describes the effect of steady and variable heat sources on TCF regeneration performance and estimates the potential of thermo-chemical energy networks, which would be particularly beneficial in buildings with high energy consumption for humidity control. This research proves the practicality of the design idea for such a network, which would be governed by centralised control, regenerated by steady or transient heat loads and capable of supplying a variety of demands in an experimental setting. The energy and economic potential of the network were also assessed, identifying temperature and humidity control application scenarios with energy savings of more than 60% compared to conventional operation and payback periods of 6.6–9.7 years. Highlights: Novel concept for thermo-chemical district network was described. An experimental test apparatus was built to investigate the principle of operation. Various scenarios for outdoor air conditions were emulated. Performance with transient and steady state heat sources was analysed. Energy and economic performance were estimated.